The hobbit : the motion picture trilogy [videorecording (Blu-Ray)] - Jackson, Peter, 1961-; Walsh, Fran, 1959-; Boyens, Philippa; Toro, Guillermo del, 1964-; McKellen, Ian; Freeman, Martin, 1971-; Armitage, Richard, 1971-; Nesbitt, James, 1965-; Stott, Ken, 1955-; Blanchett, Cate, 1969-; Holm, Ian, 1931-2020; Lee, Christopher, 1922-2015; et al. (Warner Home Video, 2018)
Follow Bilbo Baggins, who - along with the Wizard Gandalf and 13 Dwarves, led by Thorin Oakenshield - is swept into an epic and treacherous quest to reclaim the lost Dwarf Kingdom of Erebor.